Homes away from home: Jewish belonging in twentieth-century Berlin, Paris, and St. Petersburg - Wobick-Segev, Sarah (Stanford studies in Jewish history and culture, 2018)
A room of their own : friendship, fellowship and fraternity -- A place for love : autonomy, choice and partnership -- Room to grow : children, youth and informal education -- A space for Judaism : rites of passage and old-new Jewish holydays -- Rebuilding after the Shoah : the challenges of remembering and reconstruction